2009
DOI: 10.5713/ajas.2010.90145
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Feeding Solid-state Fermented Rapeseed Meal on Performance, Nutrient Digestibility, Intestinal Ecology and Intestinal Morphology of Broiler Chickens

Abstract: This trial was conducted to determine the effects of feeding a diet containing solid-state fermented rapeseed meal on performance, nutrient digestibility, intestinal ecology and intestinal morphology of broiler chickens. A mixed liquid culture, containing approximately 5 log cfu/ml Lactobacillus fermentum, Enterococcus faecium, Saccharomyces cerevisae and Bacillus subtilis was prepared in a 1:1:1:1 ratio. A basal substrate (BS) containing 75% rapeseed, 24% wheat bran and 1% brown sugar was mixed with the liqui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
150
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(201 citation statements)
references
References 29 publications
23
150
1
1
Order By: Relevance
“…This effect also is observed with the inoculation of microorganisms in SSF of various substrates [8,14]. In agreement with present investigation, [15] obtained a decrease in DM content in SSF of rapeseed paste inoculated with a culture of Lactobacillus fermentum, Enterococcus faecium, Saccharomyces cerevisiae and Bacillus subtilis. This decrease in DM was probably caused by the consumption of carbohydrates.…”
Section: Resultssupporting
confidence: 79%
“…This effect also is observed with the inoculation of microorganisms in SSF of various substrates [8,14]. In agreement with present investigation, [15] obtained a decrease in DM content in SSF of rapeseed paste inoculated with a culture of Lactobacillus fermentum, Enterococcus faecium, Saccharomyces cerevisiae and Bacillus subtilis. This decrease in DM was probably caused by the consumption of carbohydrates.…”
Section: Resultssupporting
confidence: 79%
“…However, the variation of components in oregano oil and diet are factors that can modify these effects. Chiang et al (2010) and Sayrafi et al (2011) report that the villi height increases with the amount of oregano oil in the feed, an effect that was also observed in the experiment both for 3 and 6 week old chickens.…”
Section: Height Of Intestinal Villimentioning
confidence: 73%
“…The highest villi appeared in 42 days old chickens, and the size in duodenum, jejunum and ileum was greater by 16, 22 and 70%, respectively, compared to that reported by Chiang et al (2010) and Zavarize et al (2012). Other researchers report no morphological changes at doses of 500 mg of oregano oil per kg of feed (Onderci et al 2008, Betancourt et al 2012, Emami et al 2012, Laudadio et al 2012, Wu et al 2013.…”
Section: Height Of Intestinal Villimentioning
confidence: 78%
See 1 more Smart Citation
“…The increase in CP in the present study is in agreement with the finding reported earlier by Rozan et al (1996), that the loss of dry matter at the expense of fermentable sugars during fermentation with bacteria, would result in higher percentage of CP. Later, Chiang et al (2010) also reported that CP increased slightly after fermentation, and this increase was most likely a reflection of the decline in dry matter content rather than an actual increase in protein content. In the case of amino acid contents, elevated levels were observed for some amino acids like Asp, Glu, Pro and Leu in treated CM, but the differences were not significant when compared to the control.…”
Section: Resultsmentioning
confidence: 99%